(untitled) (Journal of Health Sciences, 2013)
Introduction: Intima-media thickness (IMT) measurement of the common carotid artery (CCA) is considered as useful indicator of carotid atherosclerosis. Early detection of atherosclerosis and its associated risk factors is important to prevent stroke and heart diseases. The aim of the present study was to investigate which risk factors are better determinants of subclinical atherosclerosis, measured by common carotidartery intima media thickness (CCA-IMT).Methods: A total of 74 subjects were randomly selected in this cross – sectional study. Information on the patient’s medical history and laboratory fi ndings were obtained from their clinical records. Risk factors relevant to this study were age, gender, cigarette smoking status, diabetes, hypertension and dyslipidemia. Ultrasound scanning of carotid arteries was performed with a 7,5 MHz linear array transducer (GE Voluson730 pro). The highest value of six common carotid artery measurements was taken as the fi nal IMT. Increased CCA-IMT was defi ned when it was > 1 mm.Results: Our data demonstrated higher CCA-IMT values in male patients compared with female patients. Increased CCA-IMT was the most closely related to age (P<0.001), followed by systolic blood pressure (P=0.001), diastolic blood pressure (P=0.003) and glucose blood level (P=0.048).Conclusion: Age, gender and hypertension are the most important risk factors in development of carotid atherosclerosis. Early detection of atherosclerosis among high-risk populations is important in order to prevent stroke and heart diseases, which are leading causes of death worldwide.